1997
DOI: 10.1095/biolreprod56.5.1175
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen withdrawal Induces Macrophage Invasion in the Rabbit Corpus Luteum1

Abstract: Macrophages within the corpus luteum are associated with spontaneous luteal regression in a number of species. However, an understanding of the consequences of macrophage recruitment on the functional capacity and responsiveness of the luteal tissue has remained elusive. Here we investigate the temporal appearance of macrophages and their potential impact in corpora lutea of rabbits, in which a rapid fall in progesterone synthesis and premature regression of the corpus luteum are initiated by withdrawal of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Conversely, in this study, large numbers of apoptotic cells without any changes in the macrophage population were present at short times after PRL treatment. This agrees with previous studies in different species that suggested that the mere presence of increased numbers of macrophages is not enough to induce luteal cell death (Naftalin et al 1997, Gaytán et al 1998.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, in this study, large numbers of apoptotic cells without any changes in the macrophage population were present at short times after PRL treatment. This agrees with previous studies in different species that suggested that the mere presence of increased numbers of macrophages is not enough to induce luteal cell death (Naftalin et al 1997, Gaytán et al 1998.…”
Section: Discussionsupporting
confidence: 93%
“…There is ample evidence that macrophage invasion and phagocytosis of the apoptotic bodies takes place in regressing corpora lutea (Hehnke et al 1994, Townson et al 1996, Gaytan et al 1997, Naftalin et al 1997, Bowen et al 1999. Thus, because primary cultures of rat macrophages are feasible (Sugino et al 1996), and rat macrophage cell lines are available (Rao et al 2002), it seems reasonable to perform experiments in which transformed luteal cells are induced to die by serum deprivation in the presence of autologous macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been shown that high concentrations of ET-1 decrease P 4 production of bovine luteal cells [48], TNFα-induced ET-1 secretion from the endothelial cells may act on luteal cells as an anti-steroidogenic agent in the CL concomitant with endometrial PGF2α in cattle. Moreover, PGF2α-induced steroid reduction results in the activation of inflammatory cells followed by TNFα and interferon-γ (IFNγ) secretion in the CL of cows [49], pigs [50], and rabbits [51]. TNFα in combination w ith IFNγ reduces P4 production and the num ber of via ble cells , although TNFα alone shows little, if any, effect [33,52].…”
Section: Tnfα In Luteolysismentioning
confidence: 99%
“…The number of leukocytes increases at the time of luteolysis in the CL [49][50][51]. Interactions between TNFα and IFNγ are also considered to be important in the structural regression of the CL.…”
Section: Tnfα In Luteolysismentioning
confidence: 99%
See 1 more Smart Citation